Psychological research of fomer political prisoners - Kazlauskas, Evaldas (Genocidas ir rezistencija, 2002)
In the initial phase of the research, political prisoners were studied to assess the effects of political repression, as they can be considered the most traumatised group of all victims of Soviet repression. This group was also chosen because, compared to other groups of victims of political repression, there are very few former political prisoner survivors. The questionnaire used for this study was designed specifically for this purpose and consists of the following parts: demographic data, questions about traumatic events in their lives, standardised methodologies assessing the severity of traumatic effects, a subjective assessment of their current state of health, questions on surviving techniques that them to overcome the hardships of the repression, and the current social support.
Keywords: Soviet occupation; repressions; Gulag; political prisoners; psychological trauma